Syphilis in Pregnancy: Management and Strategies Experienced by Nurses During the Covid-19 Pandemic (Revista Contexto & Saúde, 2023)
His research deals with the management of syphilis during pregnancy in times of the Covid-19 pandemic. The objective was to identify how the experience took place and what strategies were used by PHC nurses in the city of Rio de Janeiro regarding the management and monitoring of syphilis during pregnancy during the Covid-19 pandemic. This is a study with a qualitative approach, carried out with 23 nurses who work in Primary Health Care. Data collection took place through an online questionnaire and analysis using the Content Analysis technique. The results showed that the majority of nurses were female, postgraduate and with an average of 10 years in the profession. They experienced difficulty in treating the pregnant woman and her partner, in addition to changes in the routine of health units during the pandemic. However, they do not demonstrate significant changes in the reality already experienced in relation to syphilis. The strategies indicated to continue the monitoring of syphilis in pregnant women were the partnership with community health agents to capture and actively search for pregnant women in the community and the use of information and communication technologies to provide information and health education to pregnant women in a way that remote and accessible. It can be concluded that although the changes were small in the daily care regarding syphilis, current technologies were used for remote monitoring and guidelines for the continuity of treatment of syphilis in pregnant women.
Keywords: Syphilis; Syphilis Congenital; Prenatal Care; Nurses; COVID-19